Diversity of Soil Arthropods In The Tea Plantation of PTPN XII Bantaran Blitar - Suheriyanto, Dwi; Qiptiyah, Mariatul; Prahardika, Bayu Agung (Department of Biology Science and Technology Faculty UIN Maulana Malik Ibrahim Malang, 2017)
Pruning tea leaves not only improve the productivity of the tea leaves but ecologically improve soil arthropods, which have very important role in the food chain. This study aimed to identify and analyse the diversity of soil arthropods in the tea plantation of PTPN XII Bantaran Blitar with pruning system. Observation of soil arthropods was performed by using hand sorted method on tea land with 25, 25 and 30 cm of each length, width and depth, respectively. Observations were performed at three stations, namely Pruning Year (PY) I, PY II and PY III, at which each station contains 10 observation point. The data were analysed by PAST program 3.06 version. This study found soil arthropods about 45 specimens, consisting of 15 orders, and 33 families. The most abundant order is Coleoptera, as well the role of common soil arthropods are predator. Family Formicidae is the most common family found in tea plantation. In addition, the highest of soil arthropods diversity index is in PY III, i.e. 2,58.